Global System for Atmospheric Modeling: Model Description and Preliminary Results - Marat F. Khairoutdinov; Peter N. Blossey; Christopher S. Bretherton (Journal of Advances in Modeling Earth Systems)
Abstract The extension of a cloud‐resolving model, the System for Atmospheric Modeling (SAM), to global domains is described. The resulting global model, gSAM, is formulated on a latitude‐longitude grid. It uses an anelastic dynamical core with a single reference profile (as in SAM), but its governing equations differ somewhat from other anelastic models. For quasihydrostatic flows, they are isomorphic to the primitive equations (PE) in pressure coordinates but with the globally uniform reference pressure playing the role of actual pressure. As a result, gSAM can exactly maintain steady zonally symmetric baroclinic flows that have been specified in pressure coordinates, produces accurate simulations when initialized or nudged with global reanalyses, and has a natural energy conservation equation despite the drawbacks of using the anelastic system to model global scales. gSAM employs a novel treatment of topography using a type of immersed boundary method, the Quasi‐Solid Body Method, where the instantaneous flow velocity is forced to stagnate in grid cells inside a prescribed terrain. The results of several standard tests designed to evaluate the accuracy of global models with and without topography as well as results from real Earth simulations are presented.